In the Shadow of the Laurel Wreath – Women Poets of the Old Dubrovnik (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The paper offers an overview of the poems written by the women poets of the old Dubrovnik. It points to the specific social and cultural context which marked their position in Dubrovnik from the 16th till the 18th century and foregrounded certain poetic forms, genres and styles.
Keywords: women poets; literature of Dubrovnik; Dubrovnik; cultural model; Renaissance; Enlightenment